1996
DOI: 10.1139/f96-093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic hypoxia and reduced temperature on survival and growth of burrowing mayflies, (Hexagenia limbata) (Ephemeroptera: Ephemeridae)

Abstract: Hexagenia nymphs are sensitive to hypoxia, and their abundance has been proposed as an ecosystem indicator for assessing the recovery from eutrophication of shallow, mesotrophic lakes. Acute oxygen tolerance limits are known for Hexagenia spp., but effects of prolonged exposure to sublethal levels of hypoxia are not. A series of 21-day laboratory experiments was conducted to determine the influence of hypoxic stress (range 2-12.6 mg/L dissolved oxygen) and temperature (range 4-20°C) on survival and growth of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…populations in a variety of ways: increased mortality rates, differential mortality related to nymph sizes, slower growth rates, and decreased fecundity. Winter et al (1996) found increased mortality of nymphs under even light to moderate hypoxic conditions, decreased and even negative growth rates, and that small nymphs were less likely to survive hypoxia than larger nymphs, which would impact Hexagenia spp. abundances in the succeeding 2 years.…”
Section: Discussionmentioning
confidence: 92%
“…populations in a variety of ways: increased mortality rates, differential mortality related to nymph sizes, slower growth rates, and decreased fecundity. Winter et al (1996) found increased mortality of nymphs under even light to moderate hypoxic conditions, decreased and even negative growth rates, and that small nymphs were less likely to survive hypoxia than larger nymphs, which would impact Hexagenia spp. abundances in the succeeding 2 years.…”
Section: Discussionmentioning
confidence: 92%
“…1) fits with results for other insects that have been studied ). The fruitfly D. melanogaster, beetles Z. morio, Tenebrio molitor, and Cotinis texana, the tobacco hornworm moth M. sexta and the mayfly Hexagenia limbata all demonstrate decreased body sizes when reared under hypoxia (Winter et al 1996;Peck and Maddrell 2005;Harrison et al 2009). The mechanisms behind the hypoxia-induced decrease in size are still poorly understood, though it has been shown in D. melanogaster that both cell size and cell number decrease in hypoxia (Peck and Maddrell 2005;Heinrich et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown the target taxa, especially mayflies, fingernail clams, and midges, to be ecologically important as fish and waterfowl food, biological indicators, and converters of phytoplankton and bacteria to higher energy pathways (Hoopes 1960;Fremling 1964Fremling , 1989Jude 1968;Ranthum 1969;Thompson 1973;Anderson et al 1978;Sandusky and Sparks 1979;Reice and Wohlenberg 1992;Rosenberg and Resh 1993;Winter et al 1996;Diggins and Stewart 1998;Schloesser and Nalepa 2001;Tyson and Knight 2001). For these reasons, there is much interest in tracking the abundance of these taxa.…”
Section: Discussionmentioning
confidence: 99%